Penggunaan Mit App Inventor untuk Merancang Aplikasi Pemutar Musik Berbasis Android - Elsye Nissi Waoma; Ahmad Kamal (Journal Of Informatics And Busisnes, 2023)
Music has now become a way of life for everyday people. Where is society Download music via the internet/website. However, the public does not know whether the music is downloaded via the internet whether it's original from the music producer or not. Good music to hear is music original/original. And now with the Spotify music streaming application, users can listen to music whose sound quality is guaranteed because, Spotify is a top copyright provider uploaded music. To enjoy the Spotify music streaming application service, users are required pay for the service on a monthly basis, but Spotify offers a free or free service with a term 30 days for new users who register on the Spotify Website. One technology that is rarely used by the public is the media Android based music player. This training aims to train the community in create innovative, attractive, and Android-based music player media fun for society